Crisis Management of Transmart Mataram Public Relation in Increasing the Sale Target After Lombok Earthquake Disaster - Khairunnas Mauliah; Arifuddin Sahidu; eka Putri Paramitha (JCommsci - Journal Of Media and Communication Science, 2018)
Earthquake is one of the factors that can cause a crisis for a company. One of the companies that experienced a crisis due to the earthquake in Lombok was Mataram Transmart. Lombok earthquake decreased the sales and customer debts. The purpose of this study was to determine crisis management carried out by the Public Relations Transmart Mataram in increasing sales after the earthquake in Lombok, with a research method that is descriptive. The results showed that from some of the activities carried out by the Public Relations and Transmart Mataram management team starting from planning, investigating (fact finding), identifying the symptoms of crisis emergence, coordinating crisis control, and maintaining good relations with internal and external public companies . After doing all aspects of the crisis management it was seen that there was an increase in sales after the earthquake. Previously during the crisis, the company experienced a decrease in sales turnover, after the earthquake sales turnover began to increase to approximately 15%. However, this increase has not been said to be fully increased because it has not reached the sales target as before the crisis in the company. Keywords: crisis management; public relations, Transmart Mataram, natural disaster